The Potentials of Derby Eland ( Faurotragus dcrbianus) For Commercial Hush Meat Production In Jos Wildlife Park, Nigeria (2008)
Most conservation centres in Nigeria are economically dependent on governmental and non governmental organizations for sponsorship as opportunities to generate revenues for conservation and the much needed protein for the growing population are being neglected and /or wasted This work focuses on the potentials of derby eland (Taurotragus derbiamis) Jor commercial bush meat production in Jos Wildlife Park. Nigeria. The data for this study were collected through observation, review of records and indepth interview of experienced wildlife officers. Data obtained were analyzed using descriptive statistics. Results show that derby eland has a favourable breeding trend for commercial meal production in Jos wildlife Park. No infant mortality of the species was recorded in Jos wildlife Park between 1979 and 2005 The mortality of the species recorded in the Park were cases of an elderly cow that died during parturition and a bull that was called in 2005 Both dead individuals of the species lived up to 25 years which is the life span of derby eland in the wild Derby eland feeds on vegetation and feed supplement composed of maize, soybean and groundnut that are locally sourced and processed in Jos. It has good carcass quality dnd high dressing percentage Derby eland will be a sustainable source of lender and lean meat to the public because of the semi intensive management system it is subjected to, in Jos Wildlife Park The management, medication and suitability of derby eland for meat production were discussed